2019
DOI: 10.1016/j.ajhg.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Human-Disease Phenotype Map Derived from PheWAS across 38,682 Individuals

Abstract: Phenome-wide association studies (PheWASs) have been a useful tool for testing associations between genetic variations and multiple complex traits or diagnoses. Linking PheWAS-based associations between phenotypes and a variant or a genomic region into a network provides a new way to investigate cross-phenotype associations, and it might broaden the understanding of genetic architecture that exists between diagnoses, genes, and pleiotropy. We created a network of associations from one of the largest PheWASs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 53 publications
(92 reference statements)
2
52
0
Order By: Relevance
“…Such studies have a limited scope and cannot reveal the “big picture” of disease interconnections. A major breakthrough is the HDN (human disease network) study, under which a large number of diseases are systematically analyzed. The HDN studies have the potential to reveal previously unknown disease interconnections and “globally” describe diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have a limited scope and cannot reveal the “big picture” of disease interconnections. A major breakthrough is the HDN (human disease network) study, under which a large number of diseases are systematically analyzed. The HDN studies have the potential to reveal previously unknown disease interconnections and “globally” describe diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several non‐MHC RA risk alleles have shown pleiotropic effects in several disorders, including type 1 DM, MS, and lupus , and a cross‐phenotype meta‐analysis of 7 common autoimmune diseases (RA, type 1 DM, MS, lupus, psoriasis, Crohn's disease, and celiac disease) showed that ~44% of disease‐associated SNPs were shared by some of these disorders . Similarly, a study that investigated interconnections across multiple diseases in a large EHR system found that the strongest disease network (indicated by the highest number of shared SNPs) was composed of RA, type 1 DM, MS, and psoriasis . The SNPs linking these conditions mapped to 18 loci in the MHC region and 1 in PTPN22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammation is an important component of these cardiometabolic traits, and many inflammatory genes have been associated with susceptibility to some of these traits , we did not find significant genetic pleiotropy between RA and these phenotypes. An alternative explanation is that it is not a genetic predisposition toward RA, but development of the inflammatory milieu that results from disease which causes the associations with these phenotypes .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, large data sets containing genetic variants for screening by MPRAs often lack corresponding phenotypic or other relevant MyCode participants are also consented for recontact for additional research which allows for additional clinical evaluation with more targeted phenotyping to supplement the rich data set that already exists in the EHR. DiscovEHR has already been proven to be a tremendous resource for genomic discovery (Abul-Husn et al, 2018; Gusarova et al, 2018;Verma et al, 2019).…”
Section: High-throughput Methods In Splicingmentioning
confidence: 99%